2016
DOI: 10.1002/2016ja022721
|View full text |Cite
|
Sign up to set email alerts
|

The 25 April 2015 Nepal Earthquake: Investigation of precursor in VLF subionospheric signal

Abstract: We present a critical analysis of the observations and interpretation of VLF subionospheric measurements related to the main Nepal Gorkha earthquake which occurred on 25 April 2015 (Mw7.8) and its major aftershock on 12 May 2015 (Mw7.3). The VLF narrowband signal used is from North West Cape (NWC) (19.8 kHz) VLF transmitter located in Australia and recorded at Allahabad (latitude 25.41°N, longitude 81.93°E). Allahabad is located very close (~360 km) to these earthquake epicenters. Two widely used analysis, viz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…Maurya et al (2016) also suggested that there is no extreme tropospheric weather events recorded during Nepal earthquake. In addition, we also analyzed several days prior to and after the earthquake day to identify the peculiar signatures of the ionosphere during the time of earthquake than on control days.…”
Section: Data Sets and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…Maurya et al (2016) also suggested that there is no extreme tropospheric weather events recorded during Nepal earthquake. In addition, we also analyzed several days prior to and after the earthquake day to identify the peculiar signatures of the ionosphere during the time of earthquake than on control days.…”
Section: Data Sets and Methodologymentioning
confidence: 99%
“…It is noticed that no strong thermal anomalies were observed in the OLR during the time of Nepal earthquake suggesting that there is no strong gravity wave activity in the troposphere. Maurya et al (2016) also suggested that there is no extreme tropospheric weather events recorded during Nepal earthquake. Also it may be mentioned that Allahabad station is 400 km away from the epicenter of the Nepal earthquake.…”
Section: Data Sets and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…There are a few conventional analysis methods: 1) terminator time method [8] [20] and 2) nighttime fluctuation method [3] [27].…”
Section: Vlf Data Analysismentioning
confidence: 99%